Tesla: a tech company selling cars - Hoze, Maxime (2021)
Tesla’s market capitalization of $669bn as of 2. Jan. 2021isdisconnected from reality and can in our view not be justified by fundamental analysis. The 52-week share price range of $70,10-$718,71implies a story-driven valuation that has given Tesla’s share price the momentum to reach unprecedented heights. Independent of the current market valuation of Tesla we see the company with great potential for growth and innovation, as it expands its production facilities towards Europe and China and has promising developments in breakthrough battery technologies, which will permit it to keep its competitive advantages and establish itself as the continued market leader in the battery electric vehicle (BEV)market and an important player in the energy generation & storage market in the future. Having almost reached the milestone of 500.000 delivered vehicles in 2020and with ambitious expansion projects underway, we estimate that Tesla could reach close to 2 million vehicle deliveries in 2025 and3,7 million in 2035.We reach a price target for FY21 of $160,70through the APV valuation method and weighing three possible outcome scenarios that are detailed in the report.